The Public Perception Of Earthquake Disaster Mitigation In Teluk Betung Timur District In 2025 - Rifaldy Pratama Simanungkalit; Istiawati Novia Fitri; Herlina Meri (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2026)
Earthquakes have the potential to cause major damage to life, resulting in significant loss and suffering for communities. Teluk Betung Timur District is a high-risk area due to the activities of the Tarahan Fault and the Semangko Fault, but empirical studies on the perception of the local community towards disaster mitigation are still very limited. Perceptions form the basis for society to take steps or act in response to such threats. This study aims to: (1) analyze public perception of the potential for earthquakes in East Teluk Betung District, (2) analyze public perception of earthquake disaster mitigation in East Teluk Betung District. The method used in this study is a descriptive quantitative method with data analysis techniques in the form of assessment and percentages using a five-level Likert scale. The data collection techniques in this study included observation, interviews, questionnaires, and documentation, with a sample size of 100 respondents taken using simple random sampling from 11,162 households. The results of the study showed: (1) the percentage of achievement of the maximum score of perception of potential earthquake disasters in Teluk Betung Timur District was 75.31% and categorized as good perception with a positive form of perception; (2) the percentage of achievement of the maximum score of perception of earthquake disaster mitigation in Teluk Betung Timur District is 73.99%, which is included in the category of good perception with a positive perception category. These findings indicate a gap in mitigation capacity between villages, especially related to the lack of an independent early warning system and the low intensity of socialization from local governments. This study highlights the importance of increasing disaster education programs based on the spatial needs of each village and strengthening the role of the government in providing earthquake mitigation infrastructure.